Activation of dopamine D2 receptors attenuates neuroinflammation and ameliorates the memory impairment induced by rapid eye movement sleep deprivation in a murine model - Ugalde-Muñiz, Perla; Hernández-Luna, María Guadalupe; García-Velasco, Stephany; Lugo-Huitrón, Rafael; Murcia-Ramírez, Jimena; Martínez-Tapia, Ricardo Jesus; Noriega-Navarro, Roxana; Navarro, Luz (Frontiers in Neuroscience, 2022)
The proinflammatory state, which may be induced by sleep deprivation, seems to be a determining factor in the development of neurodegenerative processes. Investigations of mechanisms that help to mitigate the inflammatory effects of sleep disorders are important. A new proposal involves the neurotransmitter dopamine, which may modulate the progression of the immune response by activating receptors expressed on immune cells. This study aimed to determine whether dopamine D2 receptor (D2DR) activation attenuates the proinflammatory response derived from rapid eye movement (REM) sleep deprivation in mice. REM sleep deprivation was induced in 2-month-old male CD1 mice using the multiple platform model for three consecutive days; during this period, the D2DR receptor agonist quinpirole (QUIN) was administered (2 mg/kg/day i.p.). Proinflammatory cytokine levels were assessed in serum and homogenates of the brain cortex, hippocampus, and striatum using ELISAs. Long-term memory deficits were identified using the Morris water maze (MWM) and novel object recognition (NOR) tests. Animals were trained until learning criteria were achieved; then, they were subjected to REM sleep deprivation (RSD) and treated with QUIN for three days. Memory evocation was determined afterward. Moreover, we found RSD induced anhedonia, as measured by the sucrose consumption test, which is commonly related to the dopaminergic system. Our data revealed increased levels of proinflammatory cytokines (TNF and IL-1β) in both the hippocampus and serum from RSD mice. However, QUIN attenuated the increased levels of these cytokines. Furthermore, RSD caused a long-term memory evocation deficit in both the MWM and NOR tests. In contrast, QUIN coadministration during the RSD period significantly improved the performance of the animals. On the other hand, QUIN prevented the anhedonic condition induced by RSD. Based on our results, D2DR receptor activation protects against memory impairment induced by disturbed REM sleep by inhibiting neuroinflammation